Strategi Adaptasi dalam Menghadapi Perubahan Ekonomi Terbaru - Wulandari, Maharani; Syahrani Amelia, Nayla; Nashobi, M. Zaki; Noviyanti, Indah (Jurnal Ekonomi STIEP, 2024)
The world is undergoing significant and rapid economic change, driven by various factors such as globalization, technological advancements, and industrial disruption. These changes present challenges and opportunities for individuals, companies, and governments. To survive and thrive in this dynamic economic environment, effective adaptation strategies are needed. Recent rapid economic changes have profoundly changed business dynamics, pushing companies to develop effective adaptation strategies. This article aims to explore various adaptation approaches that can help organizations adapt to dynamic economic changes. Through a literature review and case studies, this article highlights the importance of proactive responsibility, innovation, and flexibility in facing the challenges posed by rapid economic change. Special emphasis is placed on the company's efforts to design adaptation strategies that focus on developing human resources, improving operational efficiency, and implementing relevant technologies. Thus, this article provides practical guidance for business stakeholders to better deal with changing economic dynamics.